The global collapse resistance capacity of a seismic-damaged SRC frame strengthened with an enveloped steel jacket. (October 2021) - Xu, Chengxiang; Guo, Can; Xu, Qiqi; Yang, Zhao
Abstract: In the current study, the global collapse resistance capacity of an seismic-damaged steel-reinforced concrete (SRC) frame structure strengthened with an enveloped steel jacket was investigated. In particular, an experimental study was carried out on four 3 storey by 2 bay SRC frame structures based on a destructive test under a low cyclic lateral loading. By discounting the material performance parameter, an seismic-damaged SRC frame model was developed to simulate the damage of the structure under different degrees. Furthermore, incremental dynamic analysis of the structure was conducted to quantitatively evaluate the capacity of the seismically damaged SRC frame strengthened with the enveloped steel jacket to resist global collapse. Results revealed that the ability of the undamaged structure strengthened with enveloped steel jacket to resist global collapse increased by 15.3%, while the corresponding value for the moderate earthquake damage structure was determined as 7%. In the case of severe damage, following the repair by the enveloped steel jacket reinforcement, the ability to resist global collapse reached 98.5% of the original structure. The collapse margin ratio factor of the damaged structure was able to meet the seismic design requirements following the reinforcement by the enveloped steel jacket. This demonstrates the ability of the enveloped steel jacket reinforcement to effectively enhance the SRC frame structure resistance to global collapse.